Which robust versions of sample variance and sample covariance are most appropriate for econometrics: Symmetry-based analysis - Sriboonchitta S. (2017)
© 2016 by the Mathematical Association of Thailand. All rights reserved. In many practical situations, we do not know the shape of the corresponding probability distributions and therefore, we need to use robust statistical techniques, i.e., techniques that are applicable to all possible distributions. Empirically, it turns out the the most efficient robust version of sample variance is the average value of the p-th powers of the deviations |x i - â|from the (estimated) mean â. In this paper, we use natural symmetries to provide a theoretical explanation for this empirical success, and to show how this optimal robust version of sample variance can be naturally extended to a robust version of sample covariance.